A novel p.127Val>Ile single nucleotide polymorphism in the gene and its relation to litter size in Thin-tailed Indonesian ewes - Mutasem Abuzahra; Mohammed Baqur S. Al-Shuhaib; Dwi Wijayanti; Mustofa Helmi Effendi; Imam Mustofa; Ikechukwu Benjamin Moses (Animal Bioscience)
Objective The primary objective was to identify and characterize the single nucleotide polymorphisms (SNPs) within the MTNR1A gene sequence in Thin-tailed Indonesian ewes to assess the possible association of MTNR1A gene polymorphism with litter size trait. Methods Forty-seven Thin-tailed Indonesian sheep were selected for the study. Genotyping involved collecting blood samples, and sequencing exon 2 of the MTNR1A gene. Results The study identified 19 novel SNPs, with 10 being non-synonymous variations, in the MTNR1A gene of Thin-tailed Indonesian ewes. One non-synonymous SNP (rs1087815963) showed a significant association with litter size, with the GC genotype exhibiting a higher average litter size than the GG genotype. The deleterious impact of p.Val127Ile SNP was predicted by various in silico tools that predicted a highly damaging effect of p.Val127Ile SNP on the structure, function, and stability of MTNR1A. Docking reactions showed a critical involvement of this locus with the binding with melatonin. Conclusion In conclusion, the results of our study suggest that rs1087815963 has a remarkable negative impact on the MTNR1A with a putative alteration in the binding with melatonin. Therefore, the implementation of the novel p.Val127Ile could be a useful marker in marker-assisted selection.